Nonhemostatic Activities of Factor Xa: Are There Pleiotropic Effects of Anti-FXa Direct Oral Anticoagulants?. (November 2019) - Papadaki, Styliani; Tselepis, Alexandros D.
Factor Xa (FXa) is the key serine protease of the coagulation cascade as it is the point of convergence of the intrinsic and extrinsic pathways, leading to the formation of thrombin. Factor Xa is an established target of anticoagulation therapy, due to its central role in coagulation. Over the past years, several direct oral anticoagulants (DOACs) targeting FXa have been developed. Rivaroxaban, apixaban, and edoxaban are used in clinical practice for prevention and treatment of thrombotic diseases. Increasing evidence suggests that FXa exerts nonhemostatic cellular effects that are mediated mainly through protease-activated receptors-1 and -2 and are involved in pathophysiological conditions, such as atherosclerosis, inflammation, and fibrosis. Direct inhibition of FXa by DOACs could be beneficial in these conditions. This is a narrative review that focuses on the cellular effects of FXa in various cell types and conditions, as well as on the possible pleiotropic effects of FXa-targeting DOACs.